Free vibration of laminated shell structures using spline approximation - Mohamad Hapiz Mohamed Damiri, 1990-, author 609211; K. K. Viswanathan, supervisor 606266; Fakulti Sains 8004 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Sains ) - Universiti Teknologi Malaysia, 2016